2014
DOI: 10.1371/journal.pone.0103216
|View full text |Cite
|
Sign up to set email alerts
|

CNN3 Regulates Trophoblast Invasion and Is Upregulated by Hypoxia in BeWo Cells

Abstract: CNN3 is an ubiquitously expressed F-actin binding protein, shown to regulate trophoblast fusion and hence seems to play a role in the placentation process. In this study we demonstrate that CNN3 levels are upregulated under low oxygen conditions in the trophoblast cell line BeWo. Since hypoxia is discussed to be a pro-migratory stimulus for placental cells, we examined if CNN3 is involved in trophoblast invasion. Indeed, when performing a matrigel invasion assay we were able to show that CNN3 promotes BeWo cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(57 reference statements)
2
9
0
Order By: Relevance
“…Both inhibitory and promotional effects of hypoxia on trophoblast cell invasion have been reported in earlier studies . Corresponding to several previous studies we here demonstrated that both JEG3 and BeWo trophoblast cells exerted enhanced mobility and invasiveness when exposed to 3% oxygen. The JEG3 cell line is isolated from the placental tissue of a patient with choriocarcinoma, which expresses human chorionic gonadotropin (hCG), placental lactogen and progesterone .…”
Section: Discussionsupporting
confidence: 91%
“…Both inhibitory and promotional effects of hypoxia on trophoblast cell invasion have been reported in earlier studies . Corresponding to several previous studies we here demonstrated that both JEG3 and BeWo trophoblast cells exerted enhanced mobility and invasiveness when exposed to 3% oxygen. The JEG3 cell line is isolated from the placental tissue of a patient with choriocarcinoma, which expresses human chorionic gonadotropin (hCG), placental lactogen and progesterone .…”
Section: Discussionsupporting
confidence: 91%
“…Activated Cad is also involved in regulating breast cancer cell migration and invasion [24]. Moreover, CNN3 phosphorylation leads to phosphorylation of p38 to promote trophoblast invasion [17]. Like ERK1/2, p38 can interact with actin filaments and regulate their dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the genes that are important for metastatic ability and drug resistance of GC cells, we compared the mRNA expression profiles of MKN-45, a noninvasive and drug-sensitive cell line, and MKN-28, a highly invasive and drug-resistant cell line. Among the genes differentially expressed between these two cell lines, we selected calponin 3 (CNN3) for further analysis because it was previously implicated in invasive properties of many cells [16, 17]. In this study, we found a significant correlation between CNN3 expression and cancer cell invasiveness in gastric and breast cancer (BC) cells and we demonstrated that CNN3 can positively regulate invasiveness and doxorubicin resistance in GC cells.…”
Section: Introductionmentioning
confidence: 87%
“…These can be activated by phosphorylation, and thus are involved in a variety of cellular activities [ 24 , 25 ]. CNN3 has been shown to increase the phosphorylation of ERK1/2 and p38, but it does not change JNK phosphorylation levels in the human placental trophoblast cell line, BeWo [ 26 ]. In the present study, we also found that the phosphorylation of ERK1/2 and p38 is downregulated in CNN3-knockdown cells, suggesting that CNN3 silencing downregulates the ERK1/2 and p38 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%